The Vegetative State and Stem Cells: Therapeutic Considerations - Hazell, Alan S. (Frontiers in Neurology, 2016)
The vegetative state, also known as “unresponsive wakefulness syndrome”, is considered one of the most devastating outcomes of acquired brain injury. While diagnosis of this condition is generally well-defined clinically, patients often appear to be awake despite an absence of behavioural signs of awareness, which to the family can be confusing, leading them to believe the loved one is aware of their surroundings. This inequality of agreement can be very distressing. Currently, no cure for the vegetative state is available, as a result patients may remain in this condition for the rest of their lives, which in some cases amount to decades. Recent advances in stem cell approaches for the treatment of other neurological conditions may now provide an opportunity to intervene in this syndrome. This mini review will address development of the vegetative state, its diagnosis, affected cerebral structures, and the underlying basis of how stem cells can offer therapeutic promise that would take advantage of the often long-term features associated with this maladie to effect a repair of the severely damaged circuitry. In addition, current limitations of this treatment strategy including a lack of animal models, absence of long-term basic and clinical studies that might identify benefits of stem cell treatment, and the potential for development of tumors are considered.